Economic Considerations on the Follow-Up Practice in Gynecologic Cancers. Issue 7 (September 2015) - Pagano, Eva; Sobrero, Simona; Cavallero, Camilla; Zola, Paolo; Ciccone, Giovannino
<x xml:space="preserve">Abstract</x> Objective The aim of this review was to analyze the existing literature on the cost of follow-up in gynecology oncology. Methods/materials We performed a literature search in Medline and NHS CRD (University of Oxford) databases. Research strings were mainly based on MESH terms referring to economic studies and to neoplasms follow-up/aftercare and cancer recurrences. Two independent searches were performed for ovarian neoplasm and uterine neoplasm. Some studies were also identified among the references of the selected articles. Potentially relevant studies were identified based on the title and abstract by 2 independent readers. Results Finally, the reviewing process selected 2 studies on gynecologic cancers in general, including uterine and ovarian cancers, 3 specific on ovarian cancer, 7 on endometrium, and 9 on cervix. The identified economic literature on economic evaluation of gynecologic cancer follow-up procedures showed to be based on weak evidence of effectiveness and to lack formal methodological approaches. In general, such literature is quite recent, relies on small sample observational studies, and suffers from a lack of financial support. Conclusions There are few available lights in economic considerations on gynecologic cancer follow-up, represented by all the published studies, and many shadows that require to be clarified by properly designed randomized trials including cost-effectiveness analysis.